The reality of using technology tools by graduate teachers to give lectures from the point of view of their students - Subhi Ibrahim, Hayder; Hameed Wadi, Hiba (International Journal of Psychosocial Rehabilitation, 2020)
The lecture is the basis for the transfer of information, knowledge and experience from teachers to their students, and therefore the teaching methods and methods of teaching are varied and the field of teaching is witnessing daily changes as a result of the development in the student environment and keeping pace with the acceleration of information. Graduate studies are the field that teaches advanced science and deep knowledge and therefore it may often be difficult to absorb some subjects and concepts and these difficulties and challenges have become an incentive for many graduate professors in the faculties of physical education and sports science sought to use educational technology tools such as data projectors, smart boards and personal computers as well as software such as MS PowerPoint, Ms word, Adobe Acrobat reader in an effort to keep pace with the development and also to take advantage of the skills of the tools in simplifying information and increasing the motivation of learning. This study highlights the fact that these tools are used in graduate lectures and reveal the most important strengths and weaknesses and conducted the study on a sample of 160 graduate students specializing in physical education and sports sciences, a questionnaire was prepared to identify the reality of the use of postgraduate teachers of technology tools during lectures, it turns out that many teachers suffer from weakness in the use of technology tools in education, and that less than one third of the subjects are used only in technology tools, we recommend the need to establish workshops for professors of postgraduate studies on the use of technology in lectures..